2012
DOI: 10.1152/ajpregu.00137.2012
|View full text |Cite|
|
Sign up to set email alerts
|

Indirect calorimetry in laboratory mice and rats: principles, practical considerations, interpretation and perspectives

Abstract: In this article, we review some fundamentals of indirect calorimetry in mice and rats, and open the discussion on several debated aspects of the configuration and tuning of indirect calorimeters. On the particularly contested issue of adjustment of energy expenditure values for body size and body composition, we discuss several of the most used methods and their results when tested on a previously published set of data. We conclude that neither body weight (BW), exponents of BW, nor lean body mass (LBM) are su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
217
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(226 citation statements)
references
References 61 publications
4
217
0
2
Order By: Relevance
“…Energy expenditure and fuel selection Energy expenditure was ∼5-10% higher in HFD-fed animals, and analysis of covariance using [lean body mass+(0.2)×fat mass)] as a covariate [30] indicated that this difference was significant in 129X1, BALB/c and FVB/N mice. The RER was decreased in all five strains, consistent with increased lipid intake and catabolism (Table 1 and ESM Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Energy expenditure and fuel selection Energy expenditure was ∼5-10% higher in HFD-fed animals, and analysis of covariance using [lean body mass+(0.2)×fat mass)] as a covariate [30] indicated that this difference was significant in 129X1, BALB/c and FVB/N mice. The RER was decreased in all five strains, consistent with increased lipid intake and catabolism (Table 1 and ESM Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This cost of activity has been measured after detailed analysis of the relationship between total energy expenditure and intensity of activity measured quantitatively by force transducers as described in ref. 27. Therefore, we went on to analyze the musclespecific mitochondrial UCP3 expression levels (28) and observed a twofold higher expression of UCP3 in the SF1--COUP-TFII mice than their control littermates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to shifts in ventricular energetics, HF is associated with changes in whole-body energy balance (37,38). To assess the impact of chronic NMN supplementation on whole-body energy metabolism in these mouse models, we comprehensively measured several parameters of respiration using indirect calorimetry, including respiratory exchange (i.e., oxygen consumption, VO 2 , to carbon dioxide release, VCO 2 ), food intake, and activity (39,40). Energy balance is achieved when energy intake (i.e., parameter: food intake, Supplemental Figure 4A Figure 5A; heat expenditure, Supplemental Figure 4B; and locomotive activity Supplemental Figure 4C).…”
Section: Nmn Improves Cardiac Energy Generation and Utilization In A mentioning
confidence: 99%